THE EFFECT OF FINANCIAL DEEPENING, FOREIGN DIRECT INVESTMENT, AND INTEREST RATES ON ECONOMIC GROWTH IN INDONESIA - Diana Hafi Zahri Putri; Jihad Lukis Panjawa (Transpublika Publisher, 2022)
Economic growth determines the extent to which the activities of the economy are able to manifest additional income and sustainable economic development. Therefore, it cannot be separated from the existence of the financial sector, foreign direct investment, and interest rates for the economy. This study aims to determine the effect of financial deepening, foreign direct investment, and interest rates on economic growth in Indonesia in 1988-2020. Empirically, this study uses time series data with the Error Correction Model Engle-Granger (ECM-EG) method. The results show that financial deepening, FDI, and interest rates have a significant effect on economic growth. The variables of FDI and interest rates have a positive and significant effect on economic growth, while financial deepening has a negative and significant effect on economic growth. Likewise, national economic policies must be directed at maintaining overall economic activity and achieving sustainable growth.